Yeast mitochondrial outer membrane specifically binds cytoplasmically-synthesized precursors of mitochondrial proteins - Riezman, Howard (1983)
The precursor of cytochrome b(2) (a cytoplasmically-synthesized mitochondrial protein) binds to isolated mitochondria or to isolated outer membrane vesicles. Binding does not require an energized inner membrane, is diminished by trypsin treatment of the membranes and is not observed with the partially processed (intermediate) form of the cytochrome b(2) precursor or with non-mitochondrial proteins. Upon energization of the mitochondria, the bound precursor is imported and cleaved to the mature form. Similar results were obtained with the precursor of citrate synthase. This receptor-like binding activity was present in isolated outer, but not inner membrane. It was solubilized from outer membrane with non-ionic detergent and reconstituted into liposomes.